Exploring The Divine Message: Quranic Studies in The Context of Islamic Scholarship - Faris, Salman (Dirasah International Journal of Islamic Studies, 2023)
This research delves into the profound realm of Quranic studies within Islamic scholarship, focusing on historical development, methodologies, and specific interpretations. The study examines the evolution of Quranic studies, elucidating its growth from the early Islamic era to contemporary times. Various methodologies employed in interpreting the Quran are scrutinized, highlighting their impact on shaping religious thought. A meticulous analysis of two prominent exegeses, Tafsir bi al-Ray, and Tafsir bi al-Mathur, reveals their intricate tapestry of evocative interpretations. The research underscores the interplay of historical and socio-political dynamics in shaping Quranic scholarship, showcasing both challenges and opportunities. Ultimately, this exploration enriches our understanding of the Quran's multifaceted significance within the Islamic tradition.